Copper and manganese : studies on calcareous sandy soils in the Gibeon district, S.W.A. - Schroder, H. R. F. D. H.(Hans Richard Ferdinand Dietrich Horlein) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1959.